Interpreting Atom Probe Data from Oxide–Metal Interfaces. (3rd September 2018) - McCarroll, Ingrid; Scherrer, Barbara; Felfer, Peter; Moody, Michael P.; Cairney, Julie M.
Abstract: Understanding oxide–metal interfaces is crucial to the advancement of materials and components for many industries, most notably for semiconductor devices and power generation. Atom probe tomography provides three-dimensional, atomic scale information about chemical composition, making it an excellent technique for interface analysis. However, difficulties arise when analyzing interfacial regions due to trajectory aberrations, such as local magnification, and reconstruction artifacts. Correlative microscopy and field simulation techniques have revealed that nonuniform evolution of the tip geometry, caused by heterogeneous field evaporation, is partly responsible for these artifacts. Here we attempt to understand these trajectory artifacts through a study of the local evaporation field conditions. With a better understanding of the local evaporation field, it may be possible to account for some of the local magnification effects during the reconstruction process, eliminating these artifacts before data analysis.